Flow characterization of gas-solid mixture in fluidized bed combustion - Permatasari, Rosyida (2007)
Fluidized bed combustion is a combustion technology used to burn solid fuels. In its most basic form, fuel particles are suspended in a hot, bubbling fluidity bed of ash and other particulate materials through which jets of air are blown to provide the oxygen required for combustion or gasification.